Gereja Inkulturatif Santo Fransiskus Asisi Berastagi Sebagai Sarana Mewujudkan Persekutuan Umat - Sitepu, Abdi Guna; Br Sagala, Cica Yola (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
This research reviews the existence of the Inculturative Church of St. Francis of Assisi Berastagi as a means of realizing community fellowship. This study aims to find out the form, function and meaning of the building of the Inculturative Church of St. Francis of Assisi Berastagi and to find out the Inculturative Church as a means of realizing community fellowship. This type of research is qualitative research. The research instruments are observation, interviews and documentation. The result is that the Karo Inculturative Church Building is a means of realizing community fellowship which can be seen from the participation and involvement of the people in all activities related to fellowship. With a church building that uses an inculturative style, people feel closer to God.